IMPLEMENTATION OF CHILD-FRIENDLY EDUCATIONAL MANAGEMENT TO DEVELOP INDEPENDENCE AND STUDENT CREATIVITY - Asep Supriatna; Agus Jaenal; Cindy Febrianthy; Saepudin; Susilawati (Indonesian Journal of Elementary Education (IJETE), 2026)
Student independence and creativity are two important aspects in educational development that need to be developed to prepare students to face future challenges. These two aspects can develop well through the implementation of child-friendly educational management, which creates an environment that supports active learning and character development. This research aims to determine the impact of implementing child-friendly education management on student independence and creativity at Integrated Islamic Elementary School (SDIT) Buah Hati. This research uses quantitative methods with descriptive research design. Data collection techniques were carried out through observation, questionnaires and interviews with students and teachers. The data sources for this research are fifth grade students and teachers at SDIT Buah Hati. The collected data was analyzed using descriptive statistical techniques to describe current conditions. The research results showed a significant increase in the aspects of independence, creativity, time discipline, ability to work together, and students' self-confidence after implementing child-friendly education management. Student independence increased by 20%, creativity increased by 20%, and time discipline and the ability to work together also showed significant improvements. The implication of this research is that the implementation of child-friendly educational management is effective in increasing student independence and creativity. Therefore, schools are expected to implement child-friendly principles in every aspect of learning to support maximum student development.